2018
DOI: 10.1073/pnas.1806082115
|View full text |Cite|
|
Sign up to set email alerts
|

Yin-and-yang bifurcation of opioidergic circuits for descending analgesia at the midbrain of the mouse

Abstract: In the descending analgesia pathway, opioids are known to disinhibit the projections from the periaqueductal gray (PAG) to the rostral ventromedial medulla (RVM), leading to suppression of pain signals at the spinal cord level. The locus coeruleus (LC) has been proposed to engage in the descending pathway through noradrenergic inputs to the spinal cord. Nevertheless, how the LC is integrated in the descending analgesia circuit has remained unknown. Here, we show that the opioidergic analgesia pathway is bifurc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 59 publications
1
24
1
1
Order By: Relevance
“…3d; n = 5 LH PV :ChR2→vlPAG mice, n = 8 LH PV :tdTomato→vlPAG mice; one-way ANOVA Bonferroni multiple comparisons test, ***p = 0.0007) suggesting that LH PV neurons regulate nociceptive processing through connections in the vlPAG. Since neuronal circuits in the PAG are crucial for opioid-induced analgesia 20,21,26,27 , we sought to examine whether the LH PV →vlPAG pathway engages opioidergic mechanisms to promote antinociception. To test this, LH PV :ChR2→vlPAG mice were injected subcutaneously (s.c.) with the μ-opioid receptor antagonist naltrexone (10 mg/kg, s.c.) 30 min prior to photostimulation during the hot plate test.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3d; n = 5 LH PV :ChR2→vlPAG mice, n = 8 LH PV :tdTomato→vlPAG mice; one-way ANOVA Bonferroni multiple comparisons test, ***p = 0.0007) suggesting that LH PV neurons regulate nociceptive processing through connections in the vlPAG. Since neuronal circuits in the PAG are crucial for opioid-induced analgesia 20,21,26,27 , we sought to examine whether the LH PV →vlPAG pathway engages opioidergic mechanisms to promote antinociception. To test this, LH PV :ChR2→vlPAG mice were injected subcutaneously (s.c.) with the μ-opioid receptor antagonist naltrexone (10 mg/kg, s.c.) 30 min prior to photostimulation during the hot plate test.…”
Section: Resultsmentioning
confidence: 99%
“…We then combined optogenetics and electrophysiology to demonstrate that LH PV neurons are synaptically connected to cells within the vlPAG and that activation of this LH PV →vlPAG pathway also modulates nociceptive responses to both thermal and chemical visceral noxious stimuli. Finally, since the PAG is an important site for opioid-mediated analgesia 20,21,26,27 , we investigated whether modulation of nociception by the LH PV →vlPAG pathway involved opioidergic mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple interactions between the LC-noradrenaline system and drugs affecting pain and analgesia, such as opioids and gabapentinoids, have been described at multiple avenues, including the PAG and the RVM (36). An elegant study recently uncovered that PAG neurons projecting to the LC are distinct from PAG neurons projecting to the RVM in the classical descending inhibitory pathway (152). Interestingly, while the PAG-LC pathway is modulated by opioids to suppress descending inhibition, the PAG-RVM pathway is activated by opioids to potentiate descending inhibition of spinal nociception (152).…”
Section: Ure 5)mentioning
confidence: 99%
“…Previous studies showed that vlPAG was involved in descending inhibitory or facilitatory pain modulatory pathways (Drake et al, 2016 ; Kim et al, 2018 ; Huang et al, 2019 ). Moreover, it has been proposed that an ascending pain pathway involving the vlPAG might exist (Krout and Loewy, 2000 ).…”
Section: Discussionmentioning
confidence: 97%